Approach to a self-calibrating experimental γ-ray tracking algorithm - Napiralla, P.; Brugnara, D.; Clément, E.; Egger, H.; Goasduff, A.; John, P.R.; Kern, R.; Li, H.; Pietralla, N.; Valiente-Dobón, J.J. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2020)
A first approach to a novel, self-calibrating γ-ray tracking algorithm based on experimental data and non-Gaussian behavior of geometrical scattering angles for the Advanced GAmma Tracking Array (AGATA) is presented. A brief performance test using a 137Cs source run measured with AGATA at the Grand Accélérateur National d’Ions Lourds (GANIL), France is performed. The achievable tracking performance of the novel method is compared to the Orsay Forward Tracking algorithm.